Prevalence of dental fluorosis in relation with different fluoride levels in drinking water among school going children in Sarada tehsil of Udaipur district, Rajasthan - B U Sarvaiya; D Bhayya; R Arora; D N Mehta (Wolters Kluwer Medknow Publications, 2012)
Aim: To estimate the prevalence of dental fluorosis in relation with different fluoride levels in drinking water among school going children of 6-12 years age group. Materials and Methods: Dental fluorosis was recorded using Dean's index in school children of selected villages. The drinking water samples of all the selected villages were collected in polyethylene bottles and the fluoride content of these samples was determined by fluoride ion selective method using Orion microprocessor analyser. Results: The overall prevalence of dental fluorosis was found to be 69.84%. An increase in the community fluorosis index (CFI) with corresponding increase in water fluoride content was found. Conclusion: There was an increase in prevalence of dental fluorosis with a corresponding increase in water fluoride content from 0.8 ppm to 4.1 ppm. A significantly strong positive correlation was found between CFI and fluoride concentration in drinking water.